Effect of Substrate Composition and Liquid Organic Fertilizer from Kepok Banana Peels on Growth and Yield of White Oyster Mushroom (Pleurotus ostreatus) - Nita Nur Laila; Felicitas Deru Dewanti; Nova Triani (The University of Lampung, 2026)
This study aims to determine the impact liquid organic fertilizer (LOF) from kepok banana peels on the growth and yield of white oyster mushrooms under different substrates. The study was performed under factorial completely randomized design (4 x 4) with two factors. First factor was substrate (sawdust + rice husk) composition consisting of four levels with 25% to 100% sawdust. Second factor was concentration of LOF consisting of four levels (0; 100; 150; and 200 mL/L). Observation variables included early appearance of fruit bodies, number of caps, cap diameter, and fresh weight. The experimental data were analyzed using ANOVA followed by HSD test at α = 5%. Results showed that interaction of substrate composition and concentration of LOF significantly affected the early appearance of fruit bodies and number, diameter, and fresh weight of caps at harvest period 1 and 2. Substrate composition (50% sawdust + 50% rise husk) and concentration of LOF 200 mL/L resulted the highest fresh harvest weight with a total 249.70 g/baglog for thre harvest periods. The results of this study confirm that proper substrate composition and LOF concentration is required to achieve optimal growth and yield of white oyster mushroom.